Influenza in carehome residents: applying a conceptual framework to describe barriers to the implementation of guidance on treatment and prophylaxis. (9th April 2019) - Phipps, Emily; Watson, Conall; Mearkle, Rachel; Lock, Sarah
Abstract: Background: The European Centre for Disease Prevention and Control, National Institute for Health and Care Excellence and Public Health England have all endorsed the use of antivirals for the treatment and prophylaxis of influenza for care home residents. However, implementing these guidelines in practice is often challenging. This article aims to explore what factors impact the management of care home flu outbreaks in England according to national guidelines and highlight opportunities for change. Methods: Qualitative data from notified outbreaks between September 2017 to April 2018 in the South East of England were analyzed, applying the Greenhalgh framework for barriers to guideline implementation. Summary statistics on outbreak characteristics were generated. Stakeholders were mapped out using Eden and Ackermann's grid of interest and influence. A process map was developed to describe operational pathways. Results: There was often a delay in notifying potential outbreaks to Public Health England. Clinicians cited a lack of robust evidence for the use of antivirals and the available guidelines being too unwieldy as reasons for not implementing prescribing guidance. Many high interests and high influence stakeholders are involved in the sometimes complex care pathway, requiring coordinated work and agreement before antivirals can be prescribed. Conclusions: Our findings highlight points in the care pathway that stakeholders can target to improve quality of care and increase the likelihood of national guidance being implemented. The principles described in this article can also be applied to other challenges of translating evidence into practice and cross-organisational working.